Maltreated Children and Their Families in Juvenile Dependency Court II: Maltreatment Recidivism. Issue 2 (14th March 2016) - Lawler, Jamie M.; Gehrman, Richard; Karatekin, Canan
Abstract : The most serious maltreatment cases are referred to Juvenile Dependency Court. Eighty-eight court records were coded for factors related to maltreatment recidivism, including prior involvement histories, differential response, and placement changes. Seventy-two percent of caregivers had previous involvement, which correlated with family size and number of presenting concerns. When caregivers were offered voluntary services previously, 15% were completed. Children of substance-abusing caregivers were more likely to have prior involvement with the system. On average, children experienced four placement changes. Almost half of children reunified with caregivers had to be removed by the court. Recommendations and future directions are discussed.